Expressão escrita de concluintes de curso universitário para formar professores - Marin, Alda Junqueira; Giovanni, Luciana Maria [UNESP] (Fundação Carlos Chagas, 2007)
The main purpose of this work is to report some research analyses on the lack of preparation shown by last-year students of teachers' training course to exercise their work in the first years of schooling. Conducted from the cultural study perspective, this study enables identifying the profile of these students in the specific dimension of a written text reception and production domain. Data refer to students attending the last year of a private higher basic education teacher education program, in an institution located in a city in the State of Sao Paulo, in 2005. With Sociology contributions, this study tries to critically understand this present education model, analyzing it from inside the educational institutions and their agents. Results point out deficiencies in mastering basic school contents such as reading and writing, indispensable for the future practice of teaching first graders of primary school. This is equivalent to noticing traces of failure of the teaching school system in these higher education students.

O objetivo central deste trabalho é o de relatar algumas análises de pesquisa sobre as condições que alunos concluintes de cursos de formação de professores exibem para atuar nos anos iniciais da escolaridade. realizado na perspectiva dos estudos culturais, o estudo permite traçar o perfil desse alunado na dimensão específica do domínio da recepção e produção do texto escrito. Os dados referem-se a alunos concluintes de um Curso Normal Superior privado, de instituição do interior paulista, em 2005. Com o aporte da sociologia procura-se compreender criticamente esse modelo de formação atual, analisando-o a partir de dentro das instituições formadoras e de seus agentes. Os resultados apontam a precariedade das condições de domínio dos conteúdos escolares básicos relacionados à leitura e à escrita, indispensáveis para o exercício futuro da profissão docente nos primeiros anos do ensino fundamental, o que equivale a constatar, nessa parcela do alunado do ensino superior, indícios de falência do sistema escolar de ensino.
Written production of students attending the last year of a university course to educate teachers
Keywords: PROFESSIONAL TRAINING; WRITING EXPRESSION; HIGHER NORMAL; COURSE HIGHER EDUCATION; FORMAÇÃO UNIVERSITÁRIA DE PROFESSORES; EXPRESSÃO ESCRITA; CURSO NORMAL SUPERIOR